1993
DOI: 10.1007/bf01045071
|View full text |Cite
|
Sign up to set email alerts
|

When prior knowledge and law collide: Helping jurors use the law.

Abstract: of the individual user and is not to be disseminated broadly.1 Some states (e.g., Maryland and Indiana) instruct jurors that they have the right to nullify the law and vote not guilty if they believe a guilty verdict would be unjust under the circumstances (Hans & Vidmar, 1986). This instruction is a rare exception to the expectation that jurors will base their verdicts on the law as presented by the judge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(180 citation statements)
references
References 21 publications
9
171
0
Order By: Relevance
“…Therefore, in Study 2 we explore whether explicit information about this restriction-of which real attorneys are certainly aware-leads our mock attorneys to forgo using gender to eliminate jurors. There is mixed evidence on the general effectiveness of such warnings in improving legal decision-making (e.g., Carlson & Russo, 2001;Smith, 1993;Smith & Greene, 2005). We suspected that given intuitions and stereotypes regarding juror gender-particularly in the trial of a defendant using a ''battered wife'' defense-such a warning would not decrease gender bias.…”
Section: Studymentioning
confidence: 94%
“…Therefore, in Study 2 we explore whether explicit information about this restriction-of which real attorneys are certainly aware-leads our mock attorneys to forgo using gender to eliminate jurors. There is mixed evidence on the general effectiveness of such warnings in improving legal decision-making (e.g., Carlson & Russo, 2001;Smith, 1993;Smith & Greene, 2005). We suspected that given intuitions and stereotypes regarding juror gender-particularly in the trial of a defendant using a ''battered wife'' defense-such a warning would not decrease gender bias.…”
Section: Studymentioning
confidence: 94%
“…Second, if prototypes independently predict verdicts much more powerfully than attitudes, we would do well to study interventions that hold promise for altering prototypes. For example, Vicki Smith (1993) demonstrated that mock jurors made more legally relevant decisions after she identified and described jurors' prototypes of particular crimes, refuted these prototypes point by point, and then introduced the legal definition of the crimes. Similarly, if prototypes are guiding jurors' decisions in insanity cases, and these prototypes differ meaningfully from the legal definition of insanity, then altering jurors' insanity prototypes would allow jurors to reach verdicts that are more in line with legal definitions of insanity.…”
Section: Attitudes Toward the Insanity Defensementioning
confidence: 97%
“…Similarly, some researchers have explored strategies for bringing jurors' decisions into greater accord with the law (Smith, 1993). Excluding biased jurors or attempting to make their judgments more legally relevant are important goals: goals that need not invoke personal values about the insanity defense.…”
Section: Attitudes Toward the Insanity Defensementioning
confidence: 98%
See 1 more Smart Citation
“…Rather, it provides a sound, general depiction of the process of juror decision making and story construction. This and other studies (Kuhn et al, 1994;Smith, 1991Smith, , 1993Weinstock & Cronin, 2003), however, suggest that accounts of juror decision making must consider differences not only in representations people hold, but in the cognitive ability and understanding of the means of constructing and justifying knowledge claims that mediate the representational process. As the thinking underlying juror argument skill may be amenable to improvement (Baron, 1985(Baron, , 1993Kuhn, 1999aKuhn, , 2001Stanovich, 1999), understanding jurors' reasoning should lead to optimizing it.…”
Section: Resultsmentioning
confidence: 84%